Pemberian Ekstrak Biji Alpukat (Persea americana Mill.) dan Biji Sirsak (Annona muricata L.) terhadap Mortalitas Larva Nyamuk Culex Sp - S. Nombe; Diah Karunia Binawati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
Vegetable insecticide is a natural material that is environmentally friendly. This material can be used in the prevention and control of mosquito larvae, especially Culex sp. Culex sp is the main vector of filariasis disease and dengue hemorrhagic fever (DHF). Use of natural materials is very good and environment friendly as insectcide compared with chemicals. Avocado seed extract (Persea americana Mill) is known to have secondary metabolite content of alkaloids, saponins, triterpenoids while soursop extract (Annona muricata L) in the form of acetogenin, squamocin and annonacin. This research needs to use of avocado seed extract (P. americana Mill) and soursop seed extract (A. muricata L) as larvacide of Culex sp. The aim of this research is to know the effect of avocado seed extract (P. americana Mill) and soursop seed extract (A. muricata L) to mortality of Culex sp Instar III mosquito larvae and LC50 for 24 hours. This study was an experimental study using a complete randomized design (RAL) with five treatment concentrations (0, 2, 4, 6, and 8%) avocado seed extract (P. americana Mill) and soursop extracts extract (A. muricata L) as much as five repetitions. The data obtained were analyzed by using One Way ANOVA to show the effect on the treatment. The results showed that giving of avocado seed extract (P. americana Mill) with 8% concentration (23,8 Â± 0,45 larvae) was optimal in killing Culex sp mosquito larvae. While giving soursop seed extract (A. muricata L) with 4% concentration (25 Â± 0,0 larva) optimal in killing Culex sp mosquito larvae. Avocado seed extract (P. americana Mill) has an effect as a larvacide against Culex sp. instar III with LC50 at concentration 2,486% while soursop extract (A. muricata L) with LC50 value at concentration 1,605%. Keywords: Larvacide, soursop seed extract, avocado seed extract, Culex sp